Chimeric Antigen Receptor-T Cell Mediated Bilateral Facial Nerve Palsy: A Case Report. (July 2023) - Patrick, Natalya; Bahlis, Nizar; Peters, Steven
Chimeric antigen receptor (CAR-T) cell therapy is highly effective against hematological cancers but is associated with immune mediated side effects, including neurotoxicity. The most commonly described presentations of immune cell mediated neurotoxicity syndrome (ICANS) include cortical symptoms and generally localize to the central nervous system. In this report, we present a patient with acute onset of bilateral facial nerve palsy following CAR-T cell therapy, followed by a complete clinical recovery. Aside from a temporary anisocoria, he had no other neurologic symptoms and no encephalopathy or seizures. MRI Brain was non-contributory and cerebrospinal fluid revealed a modest increase in lymphocytes without systemic leukocytosis and viral studies were all negative. He was diagnosed with bilateral facial nerve palsy secondary to CAR-T cell therapy and subsequently treated with a course of steroids. Several weeks after presentation he returned to his neurological baseline. The presentation of CAR-T cell mediated facial nerve palsy is both clinically and scientifically relevant for physicians, patients, and researchers.